STUDY OF ROAD DEVELOPMENT PRIORITY ON SOUTHERN REGION OF WEST JAVA USING MULTI CRITERIA ANALYSIS - MULIA (nim: 26911322), FAJAR
The southern region of West Java is a relatively less developed compared to the northern region. The northern region of Java itself is an economic corridor in MP3EI program with a focus on infrastructure development. When the infrastructure in the southern region is not well preserved and developed, this may induce a greater disparity. It is necessary to programe infrastructure development to overcome this problem. In this development program, the government is also facing a limited budget, so it is necessary to prioritize the budget. This study examines several factors that need to be considered in determining the priority of road development program in the southern region of West Java. In this area there are national roads and provincial roads to be developed. In this study, Multi Criteria Analysis (MCA) with Analytical Hierarchy Process (AHP) method was used for prioritizing the road develepoment program. Several criteria have been identified as applicable for this analysis, which are : (1) the economy, with the sub-criteria consisting of natural resources potential, tourism potential and the cost of road development; (2) social and environment, with the sub-criteria consisting of social and environmental conditions; (3) the network integration, with the sub-criteria consisting of the access function of roads, integration into the activities hub and integration into the transport node. According to the respondents, the most important criteria is the network integration, while the sub-criteria is natural resources potential. Prioritization of the road development program was done by comparing the performance matrix of each road segment as the multiplication of the weights of criteria with scoring results. The scenario without budget limitation (unconstrained budget), found that Bandung Ã‚Â– Batas Cianjur road segment is the first priority. And the scenario with budget limitation (constrained budget), found that the improvement of road in southern region of West Java can be done within a period of 9 years.